The first dynasty of the Sealand in Mesopotamia - Boivin, Odette ca. 20./21. Jh. (Studies in ancient Near Eastern records, 2018)
The history of mid-2nd millennium Babylonia is marked by a dire lack of sources. The Sealand kings who controlled part of it were long known to us only indirectly. A palatial archive published recently now illuminates this elusive polity from the inside. This book explores its political, economic, and religious history, as well as the transmission of its memory. It forms a basis for interpreting future finds of that period in southern Iraq